Controllable engineering of asymmetric phosphatidylserine-containing lipid vesicles using calcium cations. Issue 95 (15th November 2017) - Sun, Hai-Yuan; Deng, Geng; Jiang, Yao-Wen; Zhou, Yu; Xu, Jing; Wu, Fu-Gen; Yu, Zhi-Wu
Abstract : The presence of Ca 2+ significantly increases the flip rate of DOPS lipid molecules due to the local membrane curvature. Abstract : A novel method to produce controllable asymmetric lipid vesicles using Ca 2+ is reported. The enrichment of negatively charged phosphatidylserine (PS) molecules in the inner leaflet is found not due to charge–charge attraction, but rather a modulation effect on the occupying size of the headgroups of PS molecules.